2014
DOI: 10.1002/jssc.201400020
|View full text |Cite
|
Sign up to set email alerts
|

Study of the retention behavior of small polar molecules on different types of stationary phases used in hydrophilic interaction liquid chromatography

Abstract: The retention behavior of a large group of analytes (35) with varied properties (pKa and logP) was studied on eight hydrophilic interaction LC columns with different surfaces, stationary phase chemistries, and types of particles. The acetonitrile content (5-95%), buffer concentration (0.5-200 mM), and pH of the mobile phase (3.8 and 6.8) were evaluated for their effects on the retention behavior. The type of stationary phase had a significant impact on the selectivity and retention time of the tested analytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…As the dissociated acids interacted with the protonated 3-aminopropyl groups through ionic interaction, higher concentrations of sodium phosphate buffer improved the eluting strength of the mobile phase, which led to a decrease in retention factors. In addition, the influence of the buffer concentration on the retention of the basic and acid compounds on this column was the same as that of 3aminopropyl stationary phase [28], which also demonstrated that a great many 3-aminopropyl groups remained in this column contributed to the ion-exchange property. Most importantly, the slope of 4,4'-methyldianiline with two charges at pH 2.7 was larger than that of 4-aminobiphenyl with single charge, which further indicated the ion-exchange mechanism of the stationary phase.…”
Section: Effect Of the Buffer Concentration Of Mobile Phase On Retentionmentioning
confidence: 53%
“…As the dissociated acids interacted with the protonated 3-aminopropyl groups through ionic interaction, higher concentrations of sodium phosphate buffer improved the eluting strength of the mobile phase, which led to a decrease in retention factors. In addition, the influence of the buffer concentration on the retention of the basic and acid compounds on this column was the same as that of 3aminopropyl stationary phase [28], which also demonstrated that a great many 3-aminopropyl groups remained in this column contributed to the ion-exchange property. Most importantly, the slope of 4,4'-methyldianiline with two charges at pH 2.7 was larger than that of 4-aminobiphenyl with single charge, which further indicated the ion-exchange mechanism of the stationary phase.…”
Section: Effect Of the Buffer Concentration Of Mobile Phase On Retentionmentioning
confidence: 53%
“…The U‐shaped retention plots were observed, e.g. for beta‐blockers atenolol and propranolol , for phenolic acids and flavonoids on various polar silica bonded columns. Some examples of the plots of the retention factors of six sulfonamides and three flavonoids versus the volume fraction of the aqueous acetate buffer, φ H2O (10 mM NH 4 Ac, 0.1% HCOOH), in the aqueous–organic mobile phase, are shown in Fig.…”
Section: Dual Retention Mode Hilic–rp Mechanism On a Single Columnmentioning
confidence: 96%
“…Hydrophilic interaction columns, such as HILIC and amide columns, were well applied to separate polar analytes such as sugars (Geng et al 2014;Liu et al 2014;Rodriguez-Sanchez et al 2014) and compounds containing basic amino groups under acidic conditions (Bertuzzi et al 2014;Diez et al 2015;Mora et al 2012;Vlckova et al 2014;Yao et al 2013). An a m i d e c o l u m n w a s u s e d t o s e p a r a t e s o d i u m monofluoroacetate in infant formula under a normal phase gradient consisting of water with ammonium formate and formic acid and acetonitrile (AOAC International 2015).…”
Section: Introductionmentioning
confidence: 99%